PENGARUH RESIDU KOMPOS PISTIA DAN JERAMI PADI PERIODE TANAM KE DUA TERHADAP PERTUMBUHAN TANAMAN KAILAN (Brassica oleraceae Var.achephala.) - mohammad zulizar (AGRONISMA, 2020)
This study aims to determine the effect of kiapu and straw compost residues in various composition of the remaining (+) and without (-) administration of the second rice planting period on the growth and yield of kailan plants. The study was conducted in May to July 2019 at the green house of the Faculty of Agriculture, Islamic University of Malang, which is located at 7.5 ° latitude and 137.35 ° latitude altitude of ± 500 m asl, while the temperature during the day is 24-28 ° C and at night day temperatures range between 16-21˚C. This study used a factorial randomized block design with a control, Factor 1 = R1: 100% kiapu, R2: 75% kiapu + 25% rice straw, R3: 50% kiapu + 50% rice straw, R4: 25% kiapu + 75% rice straw, R5: 100% straw, R6: NPK. Factor 2 = T +: addition of compost mixture in period 2 and T-: without addition of compost mixture in period 2, and T-: without the addition of the 2nd period compost mixture, so there are 12 treatment combinations plus a total control of 13 treatments. In the above treatment each was repeated 3 times and each of 3 plant samples. Observation variables include; growth variable (plant length, number of leaves, leaf brush), ), production variables (total fresh weight of plants, total dry weight of plants, consumption of fresh weight, consumption dry weight and root weight) and plant quality variables (chlorophyll and vitamin C). The results showed that the addition of compost mixture in the planting period of the two rice plants had a significant influence on the growth of kailan compared to the addition of the second period of compost dispersion, , this is seen from the analysis of the growth variable; plant length, number of leaves and leaf area. Where the addition of compost has a significant effect on the longest plant length at T + at 35 HST observation age that is equal to 34.15 cm compared to T- of 29.89 cm. On the number of leaves, the average number of leaves at T + at the age of observation was 35 HST, which was 9.53 strands compared to T- as much as 9.28 strands. . In the leaf area there was an interaction at the age of 21 HST, where the average leaf area showed that the treatment of R4T + had the widest average leaf area of 376.78 cm2 but not significantly different from the treatment of R1T + of 326.12 and R2T + of 333.90 and R5T + but significantly different from R1T- at 213.04 and R5T- at 211.14 cm2. The results of the addition of compost mixture in the second planting period of rice plants have a significant effect on total fresh weight of plants, total dry weight of plants, consumption fresh weight and dry weight, but no significant effect on root fresh weight. The total fresh weight of plants and consumption fresh weights were respectively 49.25 g / tan and 39.55 g / tan. In the quality variable, namely chlorophyll content, it shows the interaction of compost mixture type and addition treatment where the highest chlorophyll content in R1T + treatment is 8.89 µgram / ml while the parameter of vitamin C content of addition treatment and type of compost mixture have significant effect individually, , where the addition of compost mixture for the second planting period showed higher vitamin C content in the hook, amounting to 13.49% compared to those without the addition of 11.73%. The compost mixture which shows the highest vitamin C content is R5 (100% rice straw) of 13.20% but not significantly different from other compost mixes except with R4 (25% kiapu + 75% rice straw) of 10.56% .